REDUCTION OF CUMULATIVE CARDIOVASCULAR RISK IN PATIENTS WITH ARTERIAL HYPERTENSION: THE ROLE OF ANGIOTENSIN CONVERTING ENZYME INHIBITORS ACCORDING TO THE NEW EUROPEAN RECOMMENDATIONS - M. N. Mamedov; N. A. Chepurina; Z. N. Tokareva; A. A. Evdokimova (Столичная издательская компания, 2015)
Conception of total cardio-vascular risk plays important role in defining tactics of arterial hypertension therapy according to the new European recommendations. Choice of antihypertensive therapy is based on meta-analysis of large clinical studies with hard end points. It is recommended to use five classes of antihypertensive drugs in mono- and combined therapy. Angiotensin converting enzyme (ACE) inhibitors keep important place in the therapy of arterial hypertension accompanying with risk factors and associated diseases. Enalapril is one of the widely used ACE inhibitors, its efficiency was proved in prospective clinical studies. In high risk patients monotherapy with Enam (enalapril, Dr. Reddy's) decreases blood pressure and leads to positive metabolic changes. This results in significant risk reduction of cardio-vascular complications.